Primary methods of internationalisation of higher legal education - A. I. Gorylev; E. V. Kalinina (Russian State Vocational Pedagogical University, 2021)
Introduction. Recent trends in the sphere of internationalisation of higher education expand theoretical insights into the dialectical nature of correlation between pedagogical science and educational practice, as well as the relationship between the general direc tions of the development of higher education, its national and regional specifics. An analysis of the experience of internationalisation of universities is required for the development of various models to modernise higher education, including legal education, and to substantiate practical recommendations for reforming the Russian higher education system. To date, an understanding has been reached of the need to internationalise higher education in the context of globalization to increase the competitiveness of the Russian higher education system, as evidenced by the Federal project to maximise the competitive position of Russian universities among the world's leading scientific and educational centres (The Russian Academic Excellence Project 5-100). Internationalisation, being the key to optimising the export potential of Russian higher education, is essential for the modernisation of legal education.Aim. The research aimed to evaluate the productivity of actual instruments of international cooperation between universities and to outline optimal approaches to the usage of successful practices of international and Russian educational space to enhance the attractiveness of Russian legal education, and, as a consequence, the creation of a sustainable competitive advantage of a higher education institution.Methodology and research methods. Complex, interdisciplinary goals and tasks of the present research predetermined the application of gnoseological and synergetic approaches to the selection of research tools. The gnoseological approach facilitated a more profound analysis of the nature of internationalisation and integration of education in the current international processes. The synergetic approach resulted in the integration of pedagogical and legal research methods to define an optimal internationalisation strategy for the training of multiskilled legal professionals.Results. The authors assessed the effectiveness of the existing ways of internationalization of Russian legal education according to foreign student demand. A comprehensive analysis of the legal, political and social aspects of the current state of attractiveness of the Russian market of educational services and the need to identify the specifics of the internationalization of higher legal education was carried out. The experience monitoring of inter-university international cooperation allowed the authors to determine the conditions for the effectiveness of joint legal programmes (creation of an innovative educational environment, project activities and a flexible management system); to analyse modern pedagogical technologies applicable to legal disciplines; to determine the best schemes used by Russian and European universities for external mobility of students and teachers; to develop the proposals for the introduction of disciplines (for Russian students) provided in foreign languages by Russian and foreign teachers; to propose measures to improve the state policy in the field of interest, aimed at stimulating Russian universities to develop international joint educational programmes.Scientific novelty. The article presented the analysis of positive and negative experiences of Russian universities in application of internationalisation key tools in legal higher education. The acknowledged internationalisation methods of higher education were systematised in general. The additional ways for the integration of Russian legal education, in particular, to the international educational space, were identified.Practical significance consists in the approbation of new methods based on competency and practice-oriented approaches. The authors developed the guidelines for the implementation of internationalisation to enhance university competitive advantage and to increase the demand for graduates in labour market.